1998
DOI: 10.1016/s0378-4290(98)00117-8
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-by-environment interaction effect on yield and its physiological bases in short-duration pigeonpea

Abstract: Short-duration pigeonpea [Cajanus cajan (L.) Millsp.] is being targeted for commercial cultivation in more diverse environments than traditional cultivars used in subsistence agriculture. As it is a relatively new crop, information on performance of recently evolved lines and hybrids across a range of environments is lacking. Thirty lines were compared for grain yield in 20 environments representing major areas of cultivation [Patancheru (178N and 728E), Gwalior (268N and 788E) and Hisar (298N and 758E)], soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…The effect of the G × E interaction on grain yield has been reported in wheat, chickpea, maize, sorghum and other crops by various authors (Heinrich et al, 1982;Chauhan et al, 1998;Arshad et al, 2003;Masood et al, 2003;Ali et al, 2005;Dehghani et al, 2006;Farshadfar and Sutka, 2006;Mohammad, 2009;Zali et al, 2011) using different approaches for the identification of stable cultivars.…”
mentioning
confidence: 98%
“…The effect of the G × E interaction on grain yield has been reported in wheat, chickpea, maize, sorghum and other crops by various authors (Heinrich et al, 1982;Chauhan et al, 1998;Arshad et al, 2003;Masood et al, 2003;Ali et al, 2005;Dehghani et al, 2006;Farshadfar and Sutka, 2006;Mohammad, 2009;Zali et al, 2011) using different approaches for the identification of stable cultivars.…”
mentioning
confidence: 98%
“…The response of subgroup in a specific environment was calculated using the sum of the estimates of the grand mean, the mean of the main effects for the genotypes in the subgroup, and the mean of the GL interaction effects of the genotypes in that subgroup (and equal to interaction effects of group G1–G3) and that location. The locations on the horizontal axis are arranged according to IPC1 scores (Gauch, 1992; Gauch and Zobel, 1997; Chauhan et al, 1998; Samonte et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…However, Sheldrake and Naraynan (1979) showed that both determinate and indeterminate types had similar inefficiencies with respect to partitioning. However, the indeterminate types had greater advantage over determinates in the environments where growing period was longer, and less so in shorter growing environments (Chauhan et al 1998). The yields in shorter growing season are often similar to that obtained in the longer season even with half the dry matter production in the former.…”
Section: Harvest Indexmentioning
confidence: 88%